Effectiveness and Parental Acceptability of Social Networking Interventions for Promoting Seasonal Influenza Vaccination Among Young Children: Randomized Controlled Trial - Liao, Qiuyan; Fielding, Richard; Cheung, Yee Tak Derek; Lian, Jinxiao; Yuan, Jiehu; Lam, Wendy Wing Tak (JMIR Publications, 2020)
BackgroundSeasonal influenza vaccination (SIV) coverage among young children remains low worldwide. Mobile social networking apps such as WhatsApp Messenger are promising tools for health interventions. ObjectiveThis was a preliminary study to test the effectiveness and parental acceptability of a social networking intervention that sends weekly vaccination reminders and encourages exchange of SIV-related views and experiences among mothers via WhatsApp discussion groups for promoting childhood SIV. The second objective was to examine the effect of introducing time pressure on mothers' decision making for childhood SIV for vaccination decision making. This was done using countdowns of the recommended vaccination timing. MethodsMothers of child(ren) aged 6 to 72 months were randomly allocated to control or to one of two social networking intervention groups receiving vaccination reminders with (SNI+TP) or without (SNI-TP) a time pressure component via WhatsApp discussion groups at a ratio of 5:2:2. All participants first completed a baseline assessment. Both the SNI-TP and SNI+TP groups subsequently received weekly vaccination reminders from October to December 2017 and participated in WhatsApp discussions about SIV moderated by a health professional. All participants completed a follow-up assessment from April to May 2018. ResultsA total of 84.9% (174/205), 71% (57/80), and 75% (60/80) who were allocated to the control, SNI-TP, and SNI+TP groups, respectively, completed the outcome assessment. The social networking intervention significantly promoted mothers' self-efficacy for taking children for SIV (SNI-TP: odds ratio [OR] 2.69 [1.07-6.79]; SNI+TP: OR 2.50 [1.13-5.55]), but did not result in significantly improved children's SIV uptake. Moreover, after adjusting for mothers' working status, introducing additional time pressure reduced the overall SIV uptake in children of working mothers (OR 0.27 [0.10-0.77]) but significantly increased the SIV uptake among children of mothers without a full-time job (OR 6.53 [1.87-22.82]). Most participants' WhatsApp posts were about sharing experience or views (226/434, 52.1%) of which 44.7% (101/226) were categorized as negative, such as their concerns over vaccine safety, side effects and effectiveness. Although participants shared predominantly negative experience or views about SIV at the beginning of the discussion, the moderator was able to encourage the discussion of more positive experience or views and more knowledge and information. Most intervention group participants indicated willingness to receive the same interventions (110/117, 94.0%) and recommend the interventions to other mothers (102/117, 87.2%) in future ConclusionsOnline information support can effectively promote mothers' self-efficacy for taking children for SIV but alone it may not sufficient to address maternal concerns over SIV to achieve a positive vaccination decision. However, the active involvement of health professionals in online discussions can shape positive discussions about vaccination. Time pressure on decision making interacts with maternal work status, facilitating vaccination uptake among mothers who may have more free time, but having the opposite effect among busier working mothers. Trial RegistrationHong Kong University Clinical Trials Registry HKUCTR-2250; https://tinyurl.com/vejv276